1999
DOI: 10.1007/s000110050401
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interleukin-1β on bradykinin-induced responses in guinea pig peritoneal macrophages

Abstract: The most likely explanation for the cytokine effects is an influence on the level of the receptor-effector coupling downstream of the agonist binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has been previously reported that BK level is increased in the peritoneal exudates induced by carrageenin in rats [40]. In vitro studies informed us that BK performed its effects on peritoneum mainly via BK-B2 receptor [39,[41][42][43]. However, BK-B2 receptors and their relation with peritoneal fibrosis had never been shown in the EPS model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that BK level is increased in the peritoneal exudates induced by carrageenin in rats [40]. In vitro studies informed us that BK performed its effects on peritoneum mainly via BK-B2 receptor [39,[41][42][43]. However, BK-B2 receptors and their relation with peritoneal fibrosis had never been shown in the EPS model.…”
Section: Discussionmentioning
confidence: 99%
“…MA express both BKR1 and BKR2 [ 50 ]. BK also induces TNF- α and IL-1 release from murine MA cell lines [ 52 , 53 ] and stimulates prostaglandin E 2 production from rat peritoneal MA [ 54 ] (Fig. 2 ).…”
Section: Innate Immune Systemmentioning
confidence: 99%
“…During inflammation, nonneuronal cells such as M ϕ produce a variety of chemical mediators that can act on nociceptive neurons [6]. On the other hand, nociceptive mediators such as bradykinin [7, 8] and substance P [9, 10] act on the immune response and M ϕ functions.…”
Section: Introductionmentioning
confidence: 99%